Anxiety, depression and stress tension screening in patients with rheumatic and musculoskeletal diseases at the onset of the 2019 coronavirus disease (COVID-19) pandemic - A. B. Borisova; T. A. Lisitsyna; D. Yu. Veltishchev; E. L. Nasonov (Научно-практическая ревматология)
The aim - screening of anxiety, depression and stress in patients with rheumatic and musculoskeletal diseases (RMD) and medical workers at the beginning of the COVID-19.Material and methods. 150 patients (men/women: 39 (26.0%)/111 (74.0%); mean age - 43.2±16.1 years) with RMD, hospitalized at the V.A. Nasonova Research Institute of Rheumatology (Moscow) from July to November 2020, and 32 relatively healthy medical workers (men/women: 3 (9.38%)/29 (90.6%), mean age - 40.7±14.6 years) as a control group was included in the study. The Hospital Anxiety and Depression Scale (HADS) and the Depression Anxiety and Stress Scale - 21 Items (DASS-21) were used for anxiety, depression and stress screening. Results. Frequency of anxiety-depressive spectrum disorders in patients with RMD was 48% (according to DASS-21) and 27.2% (according to HADS), which did not differ significantly from the control group - 46.9% and 18.8% respectively. According to the DASS-21, patients with systemic sclerosis were significantly more likely to have a combination of clinically significant anxiety, depression and stress compared to healthy control (6 (46.2%) vs 4 (12.5%); p=0.02) and patients with spondyloarthritis (6 (46.2% vs 5 (16.1%); p=0.045). The severity of anxiety was significantly higher among patients with RMD - systemic lupus erythematosus, primary Sjogren's syndrome and systemic sclerosis, according to both scales. The severity of depression, anxiety and stress was significantly higher in women with RMD, rural residents and patients taking moderate and high doses of glucocorticoids. The pathological stress level was experienced by younger medical workers (27.5±5.45 vs 45.8±13.8 years; p=0.001). The transferred coronavirus infection did not lead to an increase in the severity of depression, anxiety and stress tension among patients, however, among medical workers, the frequency of clinically significant anxiety (4 (57.1%) vs 6 (24%)) and stress (3 (42.8%) vs 5 (20%)) was 2.2-2.9 times higher in those who have been ill. When compared with the results of the similar screening by HADS in 2012, the proportion of RМD-patients with clinically significant anxiety and depression over the past 8 years and in connection with the pandemic COVID-19 has not significantly changed.Conclusion. A new threat to health, isolation and uncertainty at the beginning of the COVID-19 were an additional stressful factor for patients with RМD, however, given the high background prevalence of low-severity chronic depression with frequent onset before RМD, the factor of the COVID-19 is not a key factor in provoking mental disorders.